Myeloid Cell Classification and Therapeutic Opportunities Within the Glioblastoma Tumor Microenvironment in the Single Cell-Omics Era - Larkin, Collin J.; Arrieta, Víctor A.; Najem, Hinda; Li, Gongbo; Zhang, Peng; Miska, Jason; Chen, Peiwen; James, Charles David; Sonabend, Adam M.; Heimberger, Amy B. (Frontiers in Immunology, 2022)
The glioma tumor microenvironment (TME) is complex and heterogeneous, and multiple emerging and current technologies are being utilized for an improved comprehension and understanding of these tumors. Single cell analysis techniques such as single cell genomic and transcriptomic sequencing analysis are on the rise and play an important role in elucidating the glioma TME. These large datasets will prove useful for patient tumor characterization, including immune configuration that will ultimately influence therapeutic choices and especially immune therapies. In this review we discuss the advantages and drawbacks of these techniques while debating their role in the domain of glioma-infiltrating myeloid cells characterization and function.